Empowering of Enterprise Group in Non Malai Community at Hin Lek Fai Subdistrict, Khu Mueang District, Buriram Province of Thailand to Enhance the Economy of Cannabis Processed Products - Srisuk, Kulganya; Charoennet, Chalita; Panoram, Preecha; Sriklang, Sukchai (Journal of Ecohumanism, 2024)
This research aimed to study the potential and capability of business operations, consumer behavior, and to provide a guideline for improving the production capacity of processed cannabis products of the Non Malai Community Enterprise, Hin Lek Fai Subdistrict, Khu Mueang District, Buriram Province. The sample group used in the research included 30 producers, selected by purposive sampling and 77 consumers, determined by the Taro Yamane formula. The research tool was a questionnaire. The statistics used in the research included percentage, mean, standard deviation, T-test, and F-test. The research results showed that the overall opinion on potential and capability was at a moderate level (2.51). The areas needing improvement included product design and quality control. The overall consumer opinion on processed cannabis products was also at a moderate level (2.73), with specific areas for improvement in product design and quality control (3.77). When comparing opinions based on education level, there was a statistically significant difference at the .05 level.